Relation between Selenium and Female Fertility: A Systematic Review - Luiz Gustavo Lima; André Amaro Mamédio dos Santos; Tiago Daniel Gueiber; Ricardo Zanetti Gomes; Camila Marinelli Martins; Andrielle Cristina Chaikoski (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2022)
Abstract Objective To analyze the influence of selenium in female fertility. Data sourceA search was performed in the following databases: MEDLINE, Web of Science, Scopus, SciELO, LILACS, MDPI, ScienceDirect, and Europe PMC. The descriptors selected were "selenium" AND "female" AND "fertility". The search interval was from 1996 to 2021. Study selectionThe evaluation was performed independently by two reviewers, and a third reviewer confirmed the inclusion of papers in case of divergence between the first two reviewers. Papers were selected after the title and abstract were read, and those that met the eligibility criteria had the full text read. Data collectionThe following data was extracted: author, year of publication, country, type of study, objective, method, sample size, follow-up period, patients' mean age, inclusion and exclusion criteria, and concentration of serum and capillary selenium. The data was organized in chronological order of paper publication. Data synthesisThe number of papers identified totaled 3,800, out of which 7 were included in the systematic review. The studies indicated a positive correlation between serum selenium and antioxidant concentration in the follicular fluid, reduction in antithyroid antibodies, oocyte production and follicle number. Conclusion Selenium supplementation is promising in women with this micronutrient deficiency to promote improvement of the reproductive efficiency and prevent damage to the pregnancy. Further studies on this theme are still required.